NEMO peptide inhibits the growth of pancreatic ductal adenocarcinoma by blocking NF-κB activation. (28th December 2017) - Zhuang, Zhuonan; Li, Hao; Lee, Harold; Aguilar, Mitzi; Gocho, Takashi; Ju, Huaiqiang; Iida, Tomonori; Ling, Jianhua; Fu, Jie; Wu, Min; Sun, Yichen; Lu, Yu; et al.
Abstract: NF-κB essential modulator (NEMO) binds and regulates IκB kinase (IKK) and is required for NF-κB activation. The NEMO-binding domain peptide (NBDP) of IKK was found to inhibit NF-κB activation and promote apoptosis in cancer cells. Studies have shown that constitutive NF-κB activation, one of the signature molecular alterations in pancreatic ductal adenocarcinoma (PDAC), is a potential therapeutic target. However, preclinical and therapeutic evidence that supports direct targeting of IKK activation in therapy is lacking. The aim of this study was to determine whether the combination of NBDP and gemcitabine would sensitize pancreatic cancer to the gemcitabine. We confirmed that NBDP inhibited NF-κB activation and found that NBDP indeed promoted chemo-sensitivity to gemcitabine in PDAC. NBDP increased PARP and caspase 3 cleavage in the apoptosis pathway, increased apoptosis of PDAC cells, and suppressed PDAC cell growth in vitro. In addition, NBDP combined with gemcitabine significantly decreased levels of NF-κB activity and inhibited the growth of PDAC in vivo in an orthotopic xenograft mouse model. Mechanistic investigations showed that NBDP effectively competed with NEMO/IKKγ for binding to IKKs and thus inhibited IKK and NF-κB activation, down-regulated expression levels of Erk, and decreased PDAC cell growth. Taken together, our current data demonstrate that NBDP sensitizes human pancreatic cancer to gemcitabine by inhibiting the NF-κB pathway. NBDP is a potential adjuvant chemotherapeutic agent for treating pancreatic cancer. Highlights: NEMO-binding domain peptide (NBDP) of IKK was found to inhibit NF-κB activation and promote apoptosis in pancreatic cancer cells. The preclinical evidence supports direct targeting of IKK activation in pancreatic cancer. NBDP combined with gemcitabine decreased levels of NF-κB activity and inhibited the growth of PDAC in vivo . NBDP effectively competed with NEMO/IKKγ for binding to IKKs and thus inhibited IKK activation.